PLC Based Speed Control in a Color Sorting System: A Design and Simulation Perspective - Umaru, Kalyankolo; Marlon, Munguleni; Nansukusa, Yudaya; Asikuru, Salaama; Ritah, Nafuna; Zaina, Kalyankolo (Journal of Engineering, Technology, and Applied Science (JETAS), 2025)
For simulation purposes in Factory IO and TIA Portal, the research is tailored to emulate industrial sorting operations. In numerous industrial scenarios, sorting operations play a crucial role, with objects segregated based on various criteria such as dimensions, colors, weight, and material composition. For instance, within Thermal Power Stations, electromagnetic sorting techniques are employed to separate ferromagnetic materials from coal. This research specifically focuses on sorting goods based on color, with adjustable speed parameters to match production rates. The system is equipped with a digital display screen, providing real-time feedback on the count of sorted objects, and receives an analog speed signal from the PLC for precise control. This research is divided into two primary components, i.e. Software and Simulation in Factory IO. The software aspect involves the implementation of ladder logic programming in TIA Portal, enabling systematic control of the entire research process based on the input data sequence, while the simulation in Factory IO is encompasses the virtual representation of conveyors for object transportation and RGB color vision sensors for color detection. The entry conveyor features two branches to load objects onto the respective conveyors, directed by the sorting logic implemented in TIA Portal.